Spleen and Liver Stiffness as Noninvasive Predictors of Varices in HBV Cirrhosis - Siahaan, Billy Stinggo; Kurniawan, Juferdy; Simadibrata, Marcellus; Rizka, Aulia; Sanityoso, Andri; Rumende, Cleopas Martin; Rachman, Andhika; Shatri, Hamzah (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
Background: Esophageal varices (EV) are the most frequent complication of portal hypertension in patients with liver cirrhosis. Due to many reasons, esophagogastroduodenoscopy remains impractical for routine surveillance in everyday practice. Hence, ongoing studies into reliable non-invasive test for predicting EV are still important.Methods: A total of 71 patients with liver cirrhosis due to hepatitis B who underwent endoscopy, spleen stiffness measurement (SSM), and liver stiffness measurement (LSM) between January and April 2023 were enrolled in this study. Diagnostic applicability was assessed using the area under the receiver-operator curve (AUC) to measure and compare the performance of each measurement and combination for predicting EV, as well as to obtain the corresponding optimal prediction value.Results: This study included 71 patients with liver cirrhosis. Among them, 74.6% (53 patients) were classified as Child-Pugh A, 22.5% (16 patients) as Child-Pugh B, and 2.8% (2 patients) as Child-Pugh C. The prevalence of esophageal varices (EV) within the cohort was 71.8%. This study showed that SSM with a cut-off of 38.8 kPa had AUC 0.867 (95% CI: 0.774–0.960) (sensitivity 78.4%, specificity 80%), and LSM with a cut-off of 10.55 kPa had AUC 0.822 (95% CI: 0.701–0.943) (sensitivity 88.2%, specificity 65%).Conclusion: Spleen and liver stiffness measurements demonstrate good performance in predicting EV in patients with liver cirrhosis caused by hepatitis B.